Analisis Layanan ITSM pada Dinas Keudayaan Kota Palembang Menggunakan ITIL V4 - Muhammad Ikhsanul Iman; Mulyati, Mulyati (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
Information Technology (IT) service management plays an important role in supporting the quality and effectiveness of public services in government institutions. The Department of Culture of Palembang City has implemented information systems to manage cultural data, administrative processes, and documentation activities. However, IT service implementation still faces challenges, including the absence of standardized incident handling procedures, inconsistencies in service request fulfillment, and limited application of continual improvement practices. These conditions indicate the need for a structured evaluation of IT service management maturity. This study aims to measure the maturity level of Information Technology Service Management (ITSM) at the Department of Culture of Palembang City using the ITIL V4 framework. The assessment focuses on five key practices: Incident Management, Problem Management, Change Enablement, Service Request Management, and Continual Improvement. A descriptive quantitative approach was employed by distributing questionnaires using a five-point Likert scale to 25 respondents consisting of information system users and IT service management personnel. The results show that four practices have reached Level 3 (Defined), while Continual Improvement remains at Level 2 (Managed). Overall, the ITSM maturity level is at Level 3, indicating that IT service processes are documented and consistently implemented but still require measurable performance indicators for continuous improvement.